Złożone Sferoidy pod Działaniem Obciążeń Skupionych - S.C. Das; R. Subramanian (Engineering Transactions, 1965)
Stresses in composite spheroids of two different isotropic elastic materials, under compressive forces acting along the common axis of revolution have been obtained. The solution is in series form. Numerical results are provided.